Representations of "Black"-type Coffins in the New Kingdom - Chen, Yunyao (AUC Knowledge Fountain, 2026)
This thesis examines depictions of twenty-three owners’ “black”-type coffins depicted in tomb wall paintings from eleven Theban tombs and on eight Theban papyri dating from the Eighteenth Dynasty to the early Twenty-first Dynasty. Four research methods are employed: descriptive, analytical, comparative, and contextual. First, a stylistic and iconographic analysis identifies four phases in the evolution of the “black”-type coffins depicted in the funerary art and explores the factors that influenced these representations by comparing them with actual “black”-type coffins and relevant artistic representations. The results indicate that the representations of “black”-type coffins feature a distinct evolution pattern, which is based on decorative patterns of actual coffins but also influenced by other factors. Second, the thesis examines funerary scenes in which “black”-type coffins appear, including workshop scenes, coffin transportation, the Opening of the Mouth ritual, and the Book of the Dead. It investigates functions and roles of “black”-type coffins in these scenes. In general, the “black”-type coffins serve primarily as body containers. They also serve as substitutes for the deceased, which are similar to other anthropoid coffins and mummiform figures of the deceased. Third, the representations of “black”-type coffins are contextualized within the broader funerary culture through textual, artistic, and material evidence to explore the possible ritual use of actual anthropoid coffins. Lastly, all representations of “black”-type coffins considered in this thesis are described in detail in Appendix I with a brief introduction to their owners and sources.